Using human factors engineering and Garvin`s product quality to develop a basketball shoe taxonomy - Luczak, T.; Burch, R.; Smith, B.; Chander, H.; Carruth, D.; Lamberth, J.; Crane, C.; Bollwinkel, D.; Burgos, B. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
Garvin`s seminal work "What Does `Product Quality` Really Mean?" defines product quality based on five approaches: transcendent, product-based, user-based, manufacturing-based, and value-based. In addition to presenting five definitions of product quality, Garvin presents eight dimensions of product quality: performance, features, reliability, conformance, durability, serviceability, aesthetics, and perceived quality. The purpose of this research is to present a taxonomy for establishing product quality metrics for basketball shoes based on Garvin`s eight dimensions and the user-based definition of product quality. There is no clear explanation for what constitutes a properly fitted and usable basketball shoe. Constructing a multi-dimensional basketball shoe quality taxonomy, as presented in this paper, captures relationships between features and user needs to improve the fitness for use in basketball shoes beyond commonly-used marketing jargon. Several contextual relationships of basketball are identified and associated with the requirements of basketball players, thereby resulting in a basketball shoe quality taxonomy that defines the relationships of shoe features to user preference. This taxonomy can be used to derive what product quality means to the basketball athlete and thus improve the decision-making process for the basketball shoe wearer and coaching staff.